Designing a program for forming professional-values orientations in future bachelores of adaptive physical culture - Kartashova V.N.,; Shcherbatykh L.N., (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the priority of key organizational and methodological provisions for designing a Program for the formation of professional and value orientations among future bachelors of adaptive physical education (in the process of learning a foreign language). Methods and structure of the study. The methodology is based on axiological, personal-activity and professionally-oriented approaches to training students in the direction 49.03.02 «Physical education for persons with health problems (adaptive physical education)». The main research methods are theoretical and methodological analyzes (study and analysis of regulatory documents, innovative teaching experience), diagnostic method (questioning) to study students' attitudes towards their future profession. The experiment was conducted at the Institute of Physical Education, Sports and Life Safety of Yelets State University. I.A. Bunin in the 2022-2023 academic year. A total of 103 1st year students participated in the experiment. Results and conclusions. The main organizational and methodological provisions of the Program for the formation of professional and value orientations among future bachelors in adaptive physical education: the creation of a psychologically comfortable microclimate in a foreign language lesson for the development of a student as a moral person with clear life guidelines; an axiological approach to the selection of foreign language content, taking into account the principles of humanistic orientation, professional guidance and educational intentions.